An Analysis of Netizens’ Language Politeness in Online News Comment Sections: A Pragmatic Study - Faradina, Anggia (Journal of Linguistica, 2025)
This study aims to analyze netizens' language politeness in the comment sections of online news platforms using a pragmatic approach. With the rise of digital media as a public communication space, the freedom of expression in comment sections often features a range of linguistic behavior, from polite to impolite expressions. The research applies Brown and Levinson’s politeness theory as the analytical framework to identify strategies of positive politeness, negative politeness, as well as face-threatening acts and impoliteness. Data were collected from five leading Indonesian online news portals and analyzed qualitatively. The findings reveal that while some comments employ politeness strategies, the majority are dominated by impolite language, particularly in news related to politics and social issues. This indicates that the digital sphere has not yet fully evolved into an ethical and constructive communication environment. The study highlights the importance of digital literacy and communication ethics in fostering a healthy culture of discourse in online spaces.